Performance of a certified elementary school teacher at the country's elementary school of 064975 fields - Nazwa Maudina; budi; Viani Alya Mayshara; Nabila Adelia; Nazwa Aulia; Ikhlasul Amal (Journal of Educational Science Learning and Research, 2025)
The study aims to evaluate the performance of teachers with certificates of teaching at SDN 064975 north sumatran field cities using a qualitative descriptive approach. Studies show performance comparisons between certified teachers and honorary teachers, where certified teachers are rated more professionally supported by formal training, such as teacher's vocational training program (PPG). The findings agree with previous studies that point out that teacher certification has a positive effect on their performance and is regarded as a professional change agent in the educational world. The teacher's performance assessment through the e-performance system is rated as a step forward in developing professionalism and the quality of teaching, although there is still a challenge in the education world, such as limited access to technology and the social background of unstable students, which can be overcome with simple solutions such as using e-performance systems. Cartons of study tools and provide support to students in need.